2012
DOI: 10.1172/jci64311
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 regulates the hypothalamic-pituitary axis at multiple levels

Abstract: Sex-determining region Y (SRY) box 2 (SOX2) haploinsufficiency causes a form of hypopituitarism in humansthat is characterized by gonadotrophin deficiency known as hypogonadotrophic hypogonadism. Here, we conditionally deleted Sox2 in mice to investigate the pathogenesis of hypogonadotrophic hypogonadism. First, we found that absence of SOX2 in the developing Rathke pouch of conditional embryos led to severe anterior lobe hypoplasia with drastically reduced expression of the pituitary-specific transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 68 publications
(92 reference statements)
12
69
1
Order By: Relevance
“…Hesx1 Cre/+ ;R26 loxP-YFP/+ 18.5 dpc embryos display widespread yellow fluorescent protein (YFP) expression in the vast majority of cells of the anterior pituitary, suggesting that the Hesx1-expressing RP progenitors give rise to all hormone-producing cells (Hesx1-cell lineage). In addition to RP, Hesx1 Cre/+ ;R26 loxP-YFP/+ and Hesx1 Cre/+ ;R26 loxP-lacZ/+ embryos show reporter expression in the ventral telencephalon and preoptic hypothalamic area from 9.5 dpc (49)(50)(51). Tcf7l1 is expressed in the forebrain, including the hypothalamic area, as well as in the anterior pituitary until 14.5 dpc (37).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hesx1 Cre/+ ;R26 loxP-YFP/+ 18.5 dpc embryos display widespread yellow fluorescent protein (YFP) expression in the vast majority of cells of the anterior pituitary, suggesting that the Hesx1-expressing RP progenitors give rise to all hormone-producing cells (Hesx1-cell lineage). In addition to RP, Hesx1 Cre/+ ;R26 loxP-YFP/+ and Hesx1 Cre/+ ;R26 loxP-lacZ/+ embryos show reporter expression in the ventral telencephalon and preoptic hypothalamic area from 9.5 dpc (49)(50)(51). Tcf7l1 is expressed in the forebrain, including the hypothalamic area, as well as in the anterior pituitary until 14.5 dpc (37).…”
Section: Methodsmentioning
confidence: 99%
“…Histological processing of embryos and in situ hybridization on paraffin sections was performed as previously described (53,54). The antisense riboprobes used in this study [Gh, glycoprotein hormone α (Cga), Pomc1, Prop1, Lh, Tsh, Fgf10, Fgf8, Bmp4, LIM homeobox protein 3 (Lhx3), Bmp4, T-box 2 (Tbx2), T-box 3 (Tbx3), and Pit1] have been described (51,(53)(54)(55). Human TCF7L1 riboprobe was generated using a full-length cDNA cloned into pCMV-Sport6 (SalI 5′, NotI 3′) (clone no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the first group, the key stem-cell regulatory transcription factors SOX2 [SRY (sex determining region Y)-box 2] and SOX9 (Arnold et al 2011;Jayakody et al 2012;Pevny and Nicolis 2010) occupy a wellrecognized position. The SOX factors 'color' cells that reside in the marginal zone (MZ), which borders the cleft (Fig.…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%
“…RP contains the embryonic precursors of the pituitary gland that generate all of the hormone-producing cells of the anterior pituitary (Bilodeau et al 2009, Davis et al 2011, Jayakody et al 2012. Based on patterns of cytokeratin expression, it has been suggested that ACP may derive from remnants of RP epithelium in humans.…”
Section: Human Tumourmentioning
confidence: 99%